A CASE STUDY OF SEVEN ELEMENTARY STUDENTS IN LEARNING LISTENING SKILL THROUGH MOBILE GAMES - Mohammad Rizky Maulana; Mujahidah Ulfa; Abdulrahman Tryanti (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
This study aims to explore, describe and analyze the use of mobile game application byelementary students to support EFL (English as a Foreign Language) learning particularlylistening skill. In this study, observation and interview are utilized to obtain the data. 8(Eight) Elementary students were participated in this study. Finding shows that studentsuse mobile game application to access content such as listen to English words or sentenceby native speaker and vocabulary. The participants of this study show positive responsetoward the use of mobile game apps in learning English listening skill. They believed thatusing mobile game apps helped them in listening, vocabulary and spelling. As theimplication of this study, it is recommended to use mobile game application for EFLstudents in order to boost their interest in learning English and the apps can be one of bestmedia to teach listening for young learners.